Perception of Science Teachers in Malacca on Science Learning That Integrates Local Wisdom - Yohana Febriana Tabun; Yohanis Kristianus Tampani; Yanuarius Bria Seran; Reni Imelda Klau (Global Education Journal, 2026)
Science Education in Indonesia faces challenges regarding contextual relevance. This study aimed to describe and analyze the perceptions of Science teachers in Malaka Regency, East Nusa Tenggara, towards the integration of local wisdom (LW) into the learning process. This approach is believed to bridge universal scientific concepts with students' cultural reality. The research employed a quantitative descriptive method with a survey design. The study population was all junior and senior high school Science teachers in Malaka, with a sample of 45 teachers selected using purposive sampling. Data were collected via a validated and reliable Likert-scale questionnaire and analyzed using descriptive statistics (mean scores and percentages). The results indicate that the overall perception of Science teachers in Malaka falls into the Very Positive category (composite mean score 4.25), signaling strong support for this approach. Although teachers hold very positive understanding and attitudes regarding the benefits of integration, they face significant challenges in implementation, mainly related to the scarcity of teaching modules specifically based on Malaka's local wisdom and time constraints for developing their own contextual materials. Teachers explicitly expressed an urgent need for training on ethnoscience integration methodology and the facilitation of contextual teaching materials. The study concludes that teachers' willingness to innovate is high, but the success of the implementation requires strategic institutional support.